2011
DOI: 10.1152/ajpregu.00488.2010
|View full text |Cite
|
Sign up to set email alerts
|

Differential apoptosis-related protein expression, mitochondrial properties, proteolytic enzyme activity, and DNA fragmentation between skeletal muscles

Abstract: McMillan EM, Quadrilatero J. Differential apoptosis-related protein expression, mitochondrial properties, proteolytic enzyme activity, and DNA fragmentation between skeletal muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 73 publications
(128 reference statements)
2
47
0
1
Order By: Relevance
“…17,35 Briefly, equal protein was loaded on 12% C. Membranes were then washed with TBS-T and incubated with the appropriate horseradish peroxidase-conjugated secondary antibody (Santa Cruz Biotechnology) for 1 h at room temperature. Immunoreactive bands were visualized using Clarity Western ECL Substrate (BioRad Laboratories; Hercules, CA) or ECL Western Blot Substrate (BioVision; Milpitas, CA) and the ChemiGenius 2 Bio-Imaging System (Syngene, Cambridge, UK).…”
Section: Immunoblot Analysesmentioning
confidence: 99%
See 3 more Smart Citations
“…17,35 Briefly, equal protein was loaded on 12% C. Membranes were then washed with TBS-T and incubated with the appropriate horseradish peroxidase-conjugated secondary antibody (Santa Cruz Biotechnology) for 1 h at room temperature. Immunoreactive bands were visualized using Clarity Western ECL Substrate (BioRad Laboratories; Hercules, CA) or ECL Western Blot Substrate (BioVision; Milpitas, CA) and the ChemiGenius 2 Bio-Imaging System (Syngene, Cambridge, UK).…”
Section: Immunoblot Analysesmentioning
confidence: 99%
“…17 Absorbance was measured at 405 nm and 490 nm using a SPECTRAmax Plus spectrophotometer (Molecular Devices; Sunnyvale, CA). A positive control for DNA fragmentation (DNA-histone-complex) was included with each assay.…”
Section: Dna Fragmentationmentioning
confidence: 99%
See 2 more Smart Citations
“…In rodent skeletal muscle, expression of µ-calpain is not dependent on muscle fiber type 64) . Recently, however, McMillan and Quadrilatero 65) determined that caspase-3, -8, and -9 activity, calpain activity, and number of apoptotic cells were also significantly higher in the red compared with white gastrocnemius. In contrast, Murphy and Lamb 66) have shown that calpain-3 activity was ~1.9 times higher in individual muscle fiber segments from extensor digitorum longus (EDL) muscle compared to soleus muscle.…”
Section: Intracellular Ca 2+ and Muscle Damagementioning
confidence: 98%